2007
DOI: 10.1073/pnas.0701209104
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and evolutionary diversification of beetle horns

Abstract: Many scarab beetles produce rigid projections from the body called horns. The exaggerated sizes of these structures and the staggering diversity of their forms have impressed biologists for centuries. Recent comparative studies using DNA sequence-based phylogenies have begun to reconstruct the historical patterns of beetle horn evolution. At the same time, developmental genetic experiments have begun to elucidate how beetle horns grow and how horn growth is modulated in response to environmental variables, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(159 citation statements)
references
References 87 publications
4
149
0
1
Order By: Relevance
“…For example, in polyphenic tadpoles, carnivore versus omnivore morphs can be produced in response to several environmental variables (Pfennig 1992;Frankino and Pfennig 2001;Pfennig et al 2007), and different populations and species exposed to different environments reveal substantial variation in the production of the two morphs (Pfennig et al 2007), suggesting multiple mechanisms for morph production and maintenance. In contrast, environments with low spatiotemporal variation or in polymorphisms that are less affected by such variation, one selection mechanism may attain primacy, as is suggested by numerous studies showing 'primary' versus 'secondary' morphs, such as in alternative male morphologies (e.g., Gross 1996;Emlen et al 2005Emlen et al , 2007. In this sense, polyphenisms can be separated into those that are more extrinsically-driven by spatiotemporal variation (e.g., dispersal and trophic polyphenisms; see also Roff 1994) and those that are more intrinsically-driven by strong genotypic effects (e.g., alternative male morphologies).…”
Section: Facultative Paedomorphosis and The Evolution Of Phenotypic Vmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in polyphenic tadpoles, carnivore versus omnivore morphs can be produced in response to several environmental variables (Pfennig 1992;Frankino and Pfennig 2001;Pfennig et al 2007), and different populations and species exposed to different environments reveal substantial variation in the production of the two morphs (Pfennig et al 2007), suggesting multiple mechanisms for morph production and maintenance. In contrast, environments with low spatiotemporal variation or in polymorphisms that are less affected by such variation, one selection mechanism may attain primacy, as is suggested by numerous studies showing 'primary' versus 'secondary' morphs, such as in alternative male morphologies (e.g., Gross 1996;Emlen et al 2005Emlen et al , 2007. In this sense, polyphenisms can be separated into those that are more extrinsically-driven by spatiotemporal variation (e.g., dispersal and trophic polyphenisms; see also Roff 1994) and those that are more intrinsically-driven by strong genotypic effects (e.g., alternative male morphologies).…”
Section: Facultative Paedomorphosis and The Evolution Of Phenotypic Vmentioning
confidence: 99%
“…Salamanders have physiological mechanisms that allow them to assess and maintain homeostasis (Feder and Burggren 1992;Kikuyama et al 2005;Stiffler 2005). Such mechanisms provide an intrinsic monitor for body condition (e.g., gut fullness and blood lipid titers in the short term, and fat storage in the long term), and indirectly allow an assessment of environmental quality (Denoël et al 2002), similar to that described in insects (e.g., Emlen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beetle horns are major cuticular projections of the head and thorax and in regions in which insects normally do not produce outgrowths. (63,64) Used as weapons in male combat over females, horns are similar, and often larger, in size than more traditional appendages such as antennae, mouthparts or legs, but lack muscles, nerves or joints. However, they are not simply modified antennae, mouthparts or legs, which instead still exist alongside horns in the same organisms, and beetle horns can thus not be homologized to other structures in a straightforward manner.…”
Section: Innovation As a Byproductmentioning
confidence: 99%
“…Variation also goes beyond the level of species: individuals of the same species, even if they are of the same sex, age and size, can be different [13]. Morphological polymorphisms within species, such as wing dimorphism and weaponry variability in insects, or plumage polymorphisms in birds such as the ruff (Philomachus pugnax), have been recognized for a long time [14][15][16]. Recent studies have also found consistent behavioural differences between individuals of the same species, sex, age and size, a phenomenon that is similar to human personality [17 -19].…”
Section: Variationmentioning
confidence: 99%